KEANEKARAGAMAN DAN KEPADATAN ECHINOIDEA DAN ASTEROIDEA DI RATAAN TERUMBU KARANG PERAIRAN TONGKAINA DAN BAHOWO KOTA MANADO ( - Ailen Imanuel Eman; Erly Yosef Kaligis; Chatrien Annita Luzianna Sinjal; Billy Theodorus Wagey (Sam Ratulangi University, 2021)
The waters of Tongkaina, which are part of northern Manado's waters, are known to have mangrove, seagrass, and seaweed ecosystems. Therefore efforts are needed to manage the population and diversity of echinoderms in these waters. Echinoderms' ecology has an essential role in maintaining the marine ecosystem's balance, which plays a role in recycling nutrients. This study aimed to determine diversity, species density, species relative density, species frequency, species relative frequency, dominance, and the index of importance of Echinoidea and Asteroidea's species in the waters of the Tongkaina Village and their density. The method used in this research is the quadratic line transect method. First of all, the survey was conducted to the sampling site's location in the coral reef flats of Tongkaina Village's waters, including Tongkaina beach and Bahowo beach, before operating the sampling. Then the observation stations were determined, namely Tongkaina waters (near Batu Meja) and Bahowo waters. The quadratic line transect method is used in this research. Species of class Echinoidea and Asteroidea in the quadrat were recorded among the total of individuals, and the species is documented. This study's results indicate that six species were found, including the survey, and five species were found based on the line transect method with 182 individuals. Including Asteroidea 85 Individuals and Echinoidea 99 Individuals. Value of Diversity at station 1 has a value of H '= 1.170 with a dominance of C = 0.364, while at Station 2 has a value of H' = 1.232 and dominance value of C = 0.316. the highest density in Station 1 is Diadema savigny 1.967 ind/m2 relative 50.86%, and Linckia laevigata with the highest frequency Fi = 0.533. The highest important value index is Diadema savigny, with a value of 81.09%, while at station 2, the Protoreaster nodosus has the highest value of important value index with a value of 87.51%. These species also have the highest density of 0.933 ind/m2 and a relative number of 41.79%.Keywords: Tongkaina, Echinoderm, Line Transect Quadrat Method, Asteroidea, Echinoidea, Coral Reef Flat